Gold nanoparticles an introduction to synthesis, properties and applications - Voliani, Valerio (De Gruyter, 2020)
Gold nanoparticles provide a platform for the development of new and efficient diagnostic and therapeutic tools. This book offers a general guide to the synthesis and coating of gold nanoparticles. It describes the links between optical features and geometries of gold nanoparticles and provides a readily comprehensible connection in all the chapters between the geometry of gold nanoparticles and their final applications.
Keywords: Nanostructured materials -- Therapeutic use.; Colloidal gold.; elektronické knihy; electronic books